Factors affecting participation in active leisure activities by people with physical disabilities - Keats, Esther (My University, 2019)
Introduction This research aimed to describe the lived experiences regarding active leisure participation of disabled persons with mobility impairments residing in Gauteng, South Africa, with the purpose of determining the factors affecting their participation. South Africa has enabling legislation, to understand if engagement in active leisure is a challenge. The research method used an explorative, descriptive, qualitative methodological approach. Participants were selected using purposive sampling. Focus groups and in-depth interviews were used for data collection, and thematic analysis was used to interpret the data. Findings Three major themes emerged - i) “Meaning of leisure,” ii) “I am a thinking feeling human being not a disability,” and iii) “Participation in active leisure.” The findings indicated that the participants differed in their perception of active leisure. Their choice of active leisure was influenced by factors such as their disability, what was accessible and within their financial means, and consequently some participants felt active leisure was not a priority due to these. All participants perceived their active leisure was constrained by public emphasis on what they could not do, rather than what they could do and they rejected this negative view. Barriers and facilitators that affected their access to active leisure participation were identified. Conclusion Despite enabling legislation in South Africa, the findings of this study illustrated that PWPDs in this study faced discrimination and exclusion to active leisure participation.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Science in Occupational Therapy to the Faculty of Health Sciences, School of Therapeutic Sciences, University of the Witwatersrand, Johannesburg, 2019